Life cycle assessment of tetrapod concrete armour units - Mikhail, Engy; Younes, Nisrina; Al Adab, Maryam; Tarnini, Al Baraa; Atabay, Serter; Mortula, Md Maruf (Frontiers in Sustainable Cities, 2025)
IntroductionConcrete is widely used in coastal construction, tetrapod armour units as the top layer of breakwaters, which protect rear-side developments by dissipating wave energy. However, concrete poses environmental impacts across its life cycle. There is a remarkable gap in the literature on the Life Cycle Assessment (LCA) of concrete armour units, despite their widespread usage in coastal engineering. To address this, this study evaluates the environmental impact of tetrapod armour over its life cycle.MethodsAn LCA is undertaken using SimaPro software, applying a cradle-to-gate approach that focuses on production, transportation, and placement stages of tetrapods, concrete and steel for casting. The functional unit (FU) is “5-meter of breakwater.” Due to limited data in the literature, the Life Cycle Inventory (LCI) is mainly obtained from the ecoinvent database available on SimaPro. Energy data for the unit processes is gathered from literature and manufacturers. The Life Cycle Impact Assessment (LCIA) is undertaken using a mid-point approach in the CML-IA method. Additionally, the non-renewable fossil impact category under the Cumulative Energy Demand (CED) method is evaluated, since non-renewable resources are major contributors in tetrapod production.ResultsThe CML-IA results show that cast production emerged as the predominant contributor, comprising over 80% of the total impacts across all categories. Notably, cast production has the highest influence on non-renewable fossil impacts under CED, with a value of 2.62E+06 MJ per FU. This highlights the significant energy burden of steel in tetrapods and underscores the importance of decision-making during the production stage. Additionally, sensitivity analysis revealed that the system has low sensitivity to changes in transportation distance.DiscussionThe study confirms cast production dominates the total environmental impacts and fossil energy use. Further research is needed to analyze large quarry rocks use for the armour layers, while accounting for regional variables to obtain more reliable results. The findings emphasize the need to explore alternative materials and production methods to reduce the environmental footprint of tetrapods while maintaining their protective effectiveness in coastal construction.